ADAPTATION OF THE MORINGA PLANT TO DIFFERENT CONDITIONS - Ochilov Azizjon Shukhrat ugli,Mamaraimova Gulinoza Mamatkarim kizi (Ethiopian International Journal of Multidisciplinary Research, 2025)
this article will cover in detail the morphological, physiological and ecological adaptations of npr oleifera your plan. Npr is a plan that grows well in your hot climates and is drought tolerance, and has high nutritional value, and its adaptation mechanisms are important in global climate change conditions. The article analyzes the characteristics of the adaptation of root, leaf, and other organs see your size based on the scientific npr.